Minority Shareholder Protection, Underpricing and the Stock Market Outcomes - XU, Wenming (Journal of Advanced Research in Law and Economics; Vol 4 No 2 (2013): JARLE Volume IV Issue 2(8) Winter 2013, 2016)
This paper presents a model that a firm issues external equity, in the presence of costs of underpricing ‘asset in place’, and conducts comparative statics analysis of its decision to issue external equity at different levels of minority shareholder protection. In the model, minority shareholder protection influences the stock market outcomes through two channels: The cost of external finance and controller’s private benefits. As a result, its effects on different stock market outcomes are heterogeneous. Using a newly assembled panel data with shareholder protection index in 25 countries for 11 years, the empirical part applies system GMM estimator to a dynamic specification and confirms such divergent effects. The minority shareholder protection is negatively correlated with the number of listed firms, but is positively correlated with the stock market capitalization.
Keywords: minority shareholder protection, underpricing, equity finance, dynamic panel analysis